2023
DOI: 10.3390/biomedicines11010172
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Zirconium Dioxide Catalyzed Multicomponent Synthesis of Bioactive Pyranopyrazoles That Target Cyclin Dependent Kinase 1 in Human Breast Cancer Cells

Abstract: Small molecules are being used to inhibit cyclin dependent kinase (CDK) enzymes in cancer treatment. There is evidence that CDK is a drug-target for cancer therapy across many tumor types because it catalyzes the transfer of the terminal phosphate of ATP to a protein that acts as a substrate. Herein, the identification of pyranopyrazoles that were CDK inhibitors was attempted, whose synthesis was catalyzed by nano-zirconium dioxide via multicomponent reaction. Additionally, we performed an in-situ analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Further, the propargylation of 6-methyl-2-thiouracil (9) was achieved in refluxing ethanol:water under basic conditions. 4-hydroxy-coumarins (3a/11), upon refluxing with bromochloropropane in DMF, yields compound (12). After purification, this compound was used for the next step by treating it with propargylated 6-methyl-2-thiouracil (10) in refluxing acetone, yielding compound (13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the propargylation of 6-methyl-2-thiouracil (9) was achieved in refluxing ethanol:water under basic conditions. 4-hydroxy-coumarins (3a/11), upon refluxing with bromochloropropane in DMF, yields compound (12). After purification, this compound was used for the next step by treating it with propargylated 6-methyl-2-thiouracil (10) in refluxing acetone, yielding compound (13).…”
Section: Resultsmentioning
confidence: 99%
“…Heterocycles have been widely studied and integrated into medicinal chemistry due to their diverse biological activities, including targeting specific cellular pathways, DNA binding, alkylation, and apoptosis induction [4,5]. Presently, extensive research is focusing on various natural and synthetic heterocyclic compounds, such as pyrimidines [6][7][8], coumarins [9,10], pyrazoles [11][12][13], triazoles [14][15][16], oxadiazoles [17][18][19], and piperazines [20,21], among others, which have displayed promising biological properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sajjadi et al (2023), for instance, reported on the synthesis of dihydropyrano[2,3c]pyrazoles via Knoevenagel-Michael multiple reactions by using green catalyst Fe 3 O 4 @gC 3 N 4 for the reaction of aldehydes, phenylhydrazine, ethyl acetoacetate and malononitrile under 1 h reflux to achieve 97 % yield of product (Route 1). [51] This reaction has also been reported by using numerous catalysts such as 1,8-diazabicyclo[5.4.0]-undec-7-en-8-ium acetate ([DBU][Ac], [59] HMS/PrÀ Rh-Zr, [60] H 3 PO 4 /Al 2 O 3 , P 2 O 5 /SiO 2 , starch sulfuric acid, cellulose sulfuric acid, [61] thiourea dioxide (TUD), [62] PVCÀ EDAÀ CeIII, [63] citrus limon (lemon juice), [64] agave leaf ash extract, [65] piperidine, [66] sodium lactate, [67] NiWO 4 , [68] PBCMOamine, [69] CaO nanoparticles, [70] Fe 3 O 4 @chitosan-tannic acid bionanocomposite, [71] FSiPSS nano-catalyst, [72] nano ZrO 2 , [73] lactic acid : urea : NH 4 Cl, [74] H 4 [SiW 12 O 40 ], [75] NiFe 2 O 4 @SiO 2 À H 3 PW 12 O 40 (NFSÀ PWA), [76] Fe 3 O 4 @SiO 2 @CoSB, [77] PAN@melamine/Fe 3 O 4 nanocomposite, [78] isonicotinic acid, [79] nano-[Fe-PSMP]Cl 2 , [80] Fe 3 O 4 /MIP-202-H 4 WO 5 , [81] Zn(L-proline) 2 , [82] baker's yeast, [83] solar radiation, [84] Cu-DABP@Fe 3 O 4 /MCM-41, [85] Fe 3 O 4 @NFC@Co(II), [86] PdO/Al-SBA-15, [87] (MnCoFe 2 O 4 @Niacin-SO 3 H) + Cl À , [88] Zn-CA-MOFs [89] and Na 2 CaP 2 O 7 . [90] In 2022, Nguyen and coworkers reported different routes to the synthesis of pyrano[2,3-c]pyrazole derivatives, which involved a four-component reaction of benzyl alcohols, phenylhydrazine, ethyl acetoacetate and malononitrile with the aid of sulfonated amorphous carbon and eosin Y as c...…”
Section: Synthesis Of Pyranopyrazole and Its Derivativesmentioning
confidence: 99%
“…28,29 In our previous report, we reported the synthesis of triazolyloxadiazole I, as an anticancer agent. 30 To explore the structural diversity of the molecule we synthesized triazoles by forming a 1,2,4-triazole ring instead of a 1,3,4-oxadiazole ring and evaluated its anticancer activity targeting JNK in MCF-7 cells.…”
Section: Introductionmentioning
confidence: 99%